Stationarity Diagnostics using Functional Expansion Tallies. (August 2020) - Kumar, Shikhar; Forget, Benoit; Smith, Kord
Highlights: Monte Carlo source stationarity is determined using Functional Expansion Tallies. This FET-based approach does not require an underlying meshing scheme. The FET-based methodology correctly diagnoses stationarity for reactor problems. This diagnostic should be adopted for high-dimensional, largely asymmetric problems. Abstract: A methodology for determining fission source stationarity is presented that characterizes the behavior of higher order spatial moments of the fission source distribution using Functional Expansional Tallies (FET's). The computation of these FET's does not require a meshing scheme like traditional methods do (e.g Shannon entropy), and is computed natively within the Monte Carlo tallying routine. To determine the efficacy of this new diagnostic, stationarity behavior is analyzed for a variety of one-dimensional and two-dimensional test cases that mimic typical reactor problems. For most problems, the results from an FET-based approach are in close agreement with those from an entropy-based approach. However, for more realistic reactor configurations with higher dimensionality and strong asymmetries, a stationary fission source distribution is better predicted using an FET-based approach.